Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Corrigendum to “Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan” [J. Asia-Pac. Entomol. 29(3) (2026)102584] - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Engineering bimetallic Cobalt–Iron glycerate Co-Catalysts on bismuth vanadate for improved charge transfer and photoelectrochemical catalytic water oxidation - Tsung-Rong Kuo; He-Jin Li; Kai-Jie Chuang; Chutima Kongvarhodom; Sibidou Yougbaré; Muhammad Saukani; Hung-Ming Chen; Lu-Yin Lin (Fuel, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Mechanically robust and electrolyte-stable 2D MOF-based nanocomposite membrane with rich low-resistance highways for high-performance osmotic energy harvesting - Chia-An Lung; Guang Hui Teoh; Wen-Hung Lin; Kalon Gopinadhan; Soorathep Kheawhom; Li-Hsien Yeh (Chemical Engineering Journal, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Reconceptualizing chorioamnionitis as an immune-mediated inflammatory disorder at the maternal–fetal interface - Tzu-Ming Wang; Chung-Min Shen; Shih-Chang Lin; Wu-Shiun Hsieh; Yi-Li Hung; Jiun-Wen Guo (Inflammation Research, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Machine learning and GC–MS revealing the characteristic flavour compounds of Cheddar cheese origin-independent at different ripening periods - Xinyue Hao; Liang Liu; Olayemi Eyituoyo Dudu; Baochao Hou; Weilian Hung; Jian He; Baolei Li; Kai Lin; Huaxi Yi; Lanwei Zhang; Pimin Gong (Food Research International, 2025)

Exogenous supplementation of key membrane lipid precursors enhances freeze-drying resistance in Lacticaseibacillus paracasei K56 by modulating membrane composition - Fengzhi Qiao; Xia Ma; Ting Sun; Baolei Li; Shaolei Wang; Shichao Xuan; Pimin Gong; Weilian Hung; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Seasonal growth and biomass production of cold-tolerant Napier Grass line L2201 - Swee-Suak Ko; Tzu-Rung Li; Jo-Chi Hung; Hsien-Chang Kuo; Min-Jeng Li; Jeng-Bin Lin; Ping-Han Chung; Lin-Hsiang Lee; Yueh-Hua Lin; Hong-Ping Lin; Charles C.-K Chou; Kuo-Chen Yeh (Biomass and Bioenergy, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Comparative transcriptomic and metabolomic analyses reveal the role of acidic electrolyzed-oxidizing water in enhancing disease resistance in Phomopsis longanae Chi-infected longans - Meiling Li; Zhongqi Fan; Xiaoze Dai; Mengshi Lin; Yifen Lin; Hui Wang; Ruiling Zhuo; Yen-Con Hung; Hetong Lin; Yihui Chen (Postharvest Biology and Technology, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Targeted TGF-βR2 Silencing in the Retrotrapezoid Nucleus Mitigates Respiratory Dysfunction and Cognitive Decline in a Mouse Model of Cerebral Amyloid Angiopathy with and without Stroke - Ahmad El Hamamy; Zahid Iqbal; Ngoc Mai Le; Arya Ranjan; YuXing Zhang; Hung Wen Lin; Chunfeng Tan; Destiny Sumani; Anthony Patrizz; Louise D. McCullough; Jun Li (Translational Stroke Research, 2025)

Geothermal gas geochemistry in Southeast Tibetan Plateau margin influenced by magma chambers and fractures - Jia-Yi Wu; Hai Gang Cao; Peng Cheng Zhao; Yu Ping Guo; Xue-Gang Chen; Xiaohu Li; Jui-Fen Tsai; Pei-Ling Wang; Li-Hung Lin (Journal of Volcanology and Geothermal Research, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

Investigating the role of membrane lipid composition differences on spray drying survival in Lactobacillus bulgaricus using non-targeted Lipidomics - Fengzhi Qiao; Shaolei Wang; Jian He; Weilian Hung; Xia Ma; Pimin Gong; Jiadong Li; Ting Sun; Cristabelle De Souza; Lanwei Zhang; Kai Lin (Food Chemistry, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Acidic electrolyzed-oxidizing water treatment mitigated the disease progression in Phomopsis longanae Chi-infected longans by modulating ROS and membrane lipid metabolism - Meiling Li; Hetong Lin; Chao Wang; Yazhen Chen; Mengshi Lin; Yen-Con Hung; Yifen Lin; Zhongqi Fan; Hui Wang; Yihui Chen (Food Chemistry, 2024)

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Effects of adding Bacillus subtilis natto NTU-18 in paste feed on growth, intestinal morphology, gastrointestinal microbiota diversity, immunity, and disease resistance of Anguilla japonica glass eels - Yen-Ting Lin; Yu-Chen Hung; Li-Han Chen; Kung-Ta Lee; Yu-San Han (Fish & Shellfish Immunology, 2024)

An Automatic Approach of Video-Based Landmark Detection and Movement Analysis for Assessing Symptoms of Bradykinesia in Parkinson’s Disease - Ching-Fang Chien; Chen-Sen Ouyang; Yi-Hung Chiu; Lung-Chang Lin; Rei-Cheng Yang; Yang-Pei Chang; San-Yuan Wang; Li-Min Liou (Journal of Medical and Biological Engineering, 2024)

Exploring the food-energy-water nexus in coupled natural-human systems under climate change with a fully integrated agent-based modeling framework - Jiaorui Zhang; Y.C. Ethan Yang; Guta W. Abeshu; Hongyi Li; Fengwei Hung; Chung-Yi Lin; L. Ruby Leung (Journal of Hydrology, 2024)

Melatonin Enhanced Microglia M2 Polarization in Rat Model of Neuro-inflammation Via Regulating ER Stress/PPARδ/SIRT1 Signaling Axis - Hung-Chuan Pan; Cheng-Ning Yang; Wen-Jane Lee; Jason Sheehan; Sheng-Mao Wu; Hong-Shiu Chen; Mao-Hsun Lin; Li-Wei Shen; Shu-Hua Lee; Chin-Chang Shen; Liang-Yi Pan; Shing‑Hwa Liu; et al. (Journal of Neuroimmune Pharmacology, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Micro-scale urbanization-based risk factors for dengue epidemics - Pei-Sheng Lin; Wei-Liang Liu; Chaur-Dong Chen; Tzai-Hung Wen; Chun-Hong Chen; Li-Wei Chen; Yi-Hung Kung (International Journal of Biometeorology, 2024)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Practically Feasible Sensor-Embedded Kinetic Assessment Piano System for Quantifying Striking Force of Digits During Piano Playing - Kuan-Yin Lai; Chieh-Hsiang Hsu; Yu-Chen Lin; Chung-Hung Tsai; Cheng-Feng Lin; Li-Chieh Kuo; Fong-Chin Su (Journal of Medical and Biological Engineering, 2023)
Purpose Understanding the pathogenesis of playing-related hand disorders through investigations based on coordination and biomechanical perspectives is indispensable. This study aimed to establish a sensor-embedded kinetic assessment piano system (SeKAPS) and conduct reliability and validity tests for this system. In addition, the differences in digit coordination between professional pianists and non-musicians were investigated. Methods Twelve subminiature load cells were embedded in the middle of the 12 corresponding keys of an upright piano. A customized calibrated system with a load cell was used to establish the criterion-related validity of the SeKAPS. The reliability of the SeKAPS was determined by 22 volunteer pianists. The other ten professional pianists and ten non-musicians were recruited to indicate the feasibility of the SeKAPS to distinguish the performing differences between groups. Results The R 2 values of regression analyses for the load cells were 0.993–0.999 ( p < 0.001), indicating high validity. The ICC values of the modified keys were 0.82–0.93, indicating high reliability. The results indicate that SeKAPS is accurate in detecting the striking force of digits during piano playing. Significant differences existed in the mean peak force and mean CVs of the peak force of the specific digits between the two groups. The results showed differences in finger control strategies between the pianists and non-musicians. Conclusion The SeKAPS may provide a valuable assessment for assisting pianists in understanding digit force control and movement strategies to achieve efficient digit coordination.

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Sublethal effects of methylmercury on lateral line sensory and ion-regulatory functions in zebrafish embryos - Giun-Yi Hung; Yu-Chin Pan; Jiun-Lin Horng; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Estimating the effect of increasing ambient temperature on antimicrobial resistance in China: A nationwide ecological study with the difference-in-differences approach - Weibin Li; Chaojie Liu; Hung Chak Ho; Lin Shi; Yingchao Zeng; Xinyi Yang; Haohai Xia; Wangjian Zhang; Cunrui Huang; Lianping Yang (Science of The Total Environment, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Heavy metals in fish, rice, and human hair and health risk assessment in Wuhan city, central China - Muhammad Ubaid Ali; Chuan Wang; Yuan Li; Ruolan Li; Shaochen Yang; Li Ding; Lin Feng; Bo Wang; Ping Li; Ming Hung Wong (Environmental Pollution, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Improving Aquaculture Water Quality Using Dual-Input Fuzzy Logic Control for Ammonia Nitrogen Management - Hung-Chih Li; Ker-Wei Yu; Chang-Hua Lien; Chitsan Lin; Cheng-Ruei Yu; Sundarapandian Vaidyanathan (Journal of Marine Science and Engineering, 2023)
In this paper, a closed-loop control system using dual-input fuzzy logic theory is proposed to improve the water quality of aquaculture. The new closed-loop control system is implemented on a Raspberry-Pi-embedded platform using Python programming. The proposed closed-loop control system integrates an RS485 function, a database transfer module, a simulating variable group function, and a trigger function import to achieve savings in human resources, power, and water consumption. The proposed closed-loop control system is equipped with an ammonia nitrogen sensor and solenoid valves for the water exchange. The experimental results demonstrate that the intelligent controller can rapidly eliminate ammonia nitrogen within the range of 2.0 ppm and maintain robust control in response to changes in ammonia nitrogen excretion from a school of fish. The experimental results provide insights into the relationship between tank capacity, water exchange solenoid valves, and ammonia nitrogen degradation time, which can be used to optimize aquaculture density and improve industrialization. The experimental results demonstrate that the savings for power and water can be achieved above 95%.

A critical analysis of sources, pollution, and remediation of selenium, an emerging contaminant - Habib Ullah; Lu Lun; Audil Rashid; Noor Zada; Baoliang Chen; Asfandyar Shahab; Ping Li; Muhammad Ubaid Ali; Siyi Lin; Ming Hung Wong (Environmental Geochemistry and Health, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

Two-phase transition induced cation-disordered Li-reactive bi-metallic phosphides enabling high-performance Li-storage - Yanhong Li; Lei Zhang; Jianbin Deng; Hung-Yu Yen; Songliu Yuan; Jeng-Han Wang; Chunfu Lin; Meilin Liu; Wenwu Li (Chemical Engineering Journal, 2023)

Acidic electrolyzed water treatment suppresses Phomopsis longanae Chi-induced the decreased storability and quality properties of fresh longans through modulating energy metabolism - Meiling Li; Qin Lin; Yazhen Chen; Yihui Chen; Mengshi Lin; Yen-Con Hung; Hetong Lin (Food Chemistry, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Pod fossils of Albizia (Fabaceae: Caesalpinioideae) from the late Miocene of northern Vietnam and their phytogeographic history - Hung Ba Nguyen; Jian Huang; Truong Van Do; Gaurav Srivastava; Hoa Mai Thi Nguyen; Shu-Feng Li; Lin-Lin Chen; Minh Trung Nguyen; Hung Dinh Doan; Zhe-Kun Zhou; Tao Su (Review of Palaeobotany and Palynology, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Preliminary establishment of a mass movement warning system for Taiwan using the soil water index - Chi-Wen Chen; Ching Hung; Guan-Wei Lin; Jun-Jih Liou; Shih-Yao Lin; Hsin-Chi Li; Yung-Ming Chen; Hongey Chen (Landslides, 2022)

Long-term exercise pre-training attenuates Alzheimer’s disease–related pathology in a transgenic rat model of Alzheimer’s disease - Luodan Yang; Chongyun Wu; Yong Li; Yan Dong; Celeste Yin-Chieh Wu; Reggie Hui-Chao Lee; Darrell W. Brann; Hung Wen Lin; Quanguang Zhang (GeroScience, 2022)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Differences in immunity between pathogen-resistant and -susceptible yam cultivars reveal insights into disease prevention underlying ethylene supplementation - Shumei Hua; Zhihua Chen; Lihong Li; Kuan-Hung Lin; Yangwen Zhang; Jieyu Yang; Shi-Peng Chen (Journal of Plant Biochemistry and Biotechnology, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Piriformospora indica colonization increases the growth, development, and herbivory resistance of sweet potato (Ipomoea batatas L.) - Qing Li; Yun-Wei Kuo; Kuan-Hung Lin; Weiqun Huang; Caisheng Deng; Kai-Wun Yeh; Shi-Peng Chen (Plant Cell Reports, 2021)

Dynamic Stability of an Ocean Current Turbine System - Shueei-Muh Lin; Yang-Yih Chen; Hung-Chu Hsu; Meng-Syue Li (Journal of Marine Science and Engineering, 2020)
This paper presents a theoretical solution for the dynamic stability of the ocean current turbine system developed in Taiwan. This system is tethered to the sea floor and uses the Kuroshio Current to produce electricity. To maintain the performance of the turbine system in the presence of the Kuroshio Current, the stability of the surfaced turbine needs to be considered. The proposed system is composed of a turbine, a buoyance platform, a traction rope, and a mooring foundation. The two-dimensional theoretical solutions treat the turbine as a rigid body with a movable structure that is moored with two cables. In this model, the gravity, buoyancy, and drag force generated by the wave on the turbine structure are considered. In addition, an analytical solution is proposed for the general system. Finally, the effects of the wave on the pitch motion and dynamical stability of the ocean current turbine system are investigated.

Upregulation of miR-133a-3p in the Sciatic Nerve Contributes to Neuropathic Pain Development - Lin-Li Chang; Hung-Chen Wang; Kuang-Yi Tseng; Miao-Pei Su; Jaw-Yuan Wang; Yi-Ta Chuang; Yi-Hsuan Wang; Kuang-I Cheng (Molecular Neurobiology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Methane Seeps and Independent Methane Plumes in the South China Sea Offshore Taiwan - Susan Mau; Tzu-Hsuan Tu; Marius Becker; Christian dos Santos Ferreira; Jhen-Nien Chen; Li-Hung Lin; Pei-Ling Wang; Saulwood Lin; Gerhard Bohrmann (Frontiers in Marine Science, 2020)

Comprehensive Natural Environment and Landscape Signs in Coastal Settlement Hazard Assessment: Case of East Taiwan between the Coastal Mountain and the Pacific Ocean - Shyang-Woei Lin; Chia-Feng Yen; Chih-Hsin Chang; Li-Jin Wang; Hung-Ju Shih (Journal of Marine Science and Engineering, 2020)
In East Taiwan, coastal settlements are scattered and narrowly confined between the Coastal Mountain and the Pacific Ocean. These settlements are currently at risk as there is no room for retreat. Therefore, it is essential to conduct a comprehensive and continuous hazard assessment in these coastal residential areas. In order to avoid biased towards the natural environment, the factors that cannot easily be built within the geographic information system (GIS) database are distinguished by Unmanned Aerial Vehicle (UAV) to conduct a vulnerability assessment of threats to coastal zones. The method: we used the east coast of Taiwan as an example, through GIS and statistical analysis in land-use status, vulnerable population groups and UAV landscape signs of indicators of erosion and accumulation. Through the main output of an intuition scatter map, the erosion landscape susceptibility, economical land-use exposure, and special population groups’ ratio allowed for the easy comparison of the vulnerability, risk level and resilience between different coastal settlements. These diverse observation aspects of risk assessment results can provide prevention and control strategies that meet the different needs of coastal risk management in restricting and strengthening the land-use development of communities.

Cognitive Load of Exercise Influences Cognition and Neuroplasticity of Healthy Elderly: An Exploratory Investigation - Yi-Ping Chao; Changwei W. Wu; Li-Jung Lin; Cheng-Hung Lai; Hong-Yi Wu; Ai-Ling Hsu; Chiao-Nan Chen (Journal of Medical and Biological Engineering, 2020)
This study explored the effects of exercise with either high cognitive load or low cognitive load on cognitive performance and neuroplasticity in healthy elderly. Twenty-eight sedentary community-dwelling seniors participated in this study. Participants were assigned to one of three groups: the control group (C), low-cognitive load exercise group (LE), or high-cognitive load exercise group (HE). Individuals in both exercise groups engaged in moderate-intensity aerobic exercise for 4 months. Resting-state functional MRI and diffusion MRI were used to investigate the effects of intervention on functional and structural connectivity, respectively. Analysis of covariance with baseline, age and the education year as covariates was used to determine the effects of intervention. We found 4 months of exercise with high-cognitive load, but not exercise with low-cognitive load, improved the overall cognitive function of healthy elderly. Additionally, the HE group showed increased resting-state functional connectivity of superior frontal gyrus and anterior cingulate cortex and decreased functional connectivity of middle occipital gyrus and postcentral gyrus. The age-related alterations in local efficiency and betweenness were protected by exercise. Our findings might suggest that exercise with greater cognitive load likely results in greater training effects on cognition and brain connectivity than exercise requiring lower cognitive loads for healthy elderly.

Protective Effect of (−)Epigallocatechin-3-gallate on Rotenone-Induced Parkinsonism-like Symptoms in Rats - Hsiang-Chien Tseng; Mao-Hsien Wang; Kuo-Chi Chang; Hung-Sheng Soung; Chih-Hsiang Fang; Yi-Wen Lin; Keng-Yuan Li; Chih-Chuan Yang; Cheng-Chia Tsai (Neurotoxicity Research, 2020)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

Using in situ modification to enhance organic fouling resistance and rejection of pharmaceutical and personal care products in a thin-film composite nanofiltration membrane - Yi-Li Lin; Jia-Zheng Tsai; Chung-Hsuang Hung (Environmental Science and Pollution Research, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Extracting region-specific runout behavior and rainfall thresholds for massive landslides using seismic records: a case study in southern Taiwan - Ching Hung; Guan-Wei Lin; Ben Leshchinsky; Hsien-Li Kuo (Bulletin of Engineering Geology and the Environment, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Acoustic Emission-Feedback Planar Ultrasound System for Localized Blood–Brain Barrier Opening Monitoring - Chih-Hung Tsai; Ko-Ting Chen; Yu-Xian Lin; Yu-Chien Lin; Wen-Shiang Chen; Claude Inserra; Hao-Li Liu (Journal of Medical and Biological Engineering, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Factors regulating carbon sinks in mangrove ecosystems - Shi‐Bo Li; Po‐Hung Chen; Jih‐Sheng Huang; Mei‐Li Hsueh; Li‐Yung Hsieh; Chen‐Lu Lee; Hsing‐Juh Lin (Global Change Biology, 2018)
Mangroves are recognized as one of the richest carbon storage systems. However, the factors regulating carbon sinks in mangrove ecosystems are still unclear, particularly in the subtropical mangroves. The biomass, production, litterfall, detrital export and decomposition of the dominant mangrove vegetation in subtropical ( Kandelia obovata ) and tropical ( Avicennia marina ) Taiwan were quantified from October 2011 to July 2014 to construct the carbon budgets. Despite the different tree species, a principal component analysis revealed the site or environmental conditions had a greater influence than the tree species on the carbon processes. For both species, the net production (NP) rates ranged from 10.86 to 27.64 Mg C ha −1 year −1 and were higher than the global average rate due to the high tree density. While most of the litterfall remained on the ground, a high percentage (72%–91%) of the ground litter decomposed within 1 year and fluxed out of the mangroves. However, human activities might cause a carbon flux into the mangroves and a lower NP rate. The rates of the organic carbon export and soil heterotrophic respiration were greater than the global mean values and those at other locations. Only a small percentage (3%–12%) of the NP was stored in the sediment. The carbon burial rates were much lower than the global average rate due to their faster decomposition, indicating that decomposition played a critical role in determining the burial rate in the sediment. The summation of the organic and inorganic carbon fluxes and soil heterotrophic respiration well exceeded the amount of litter decomposition, indicating an additional source of organic carbon that was unaccounted for by decomposition in the sediment. Sediment‐stable isotope analyses further suggest that the trapping of organic matter from upstream rivers or adjacent waters contributed more to the mangrove carbon sinks than the actual production of the mangrove trees.

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Prior Visual Experience Modulates Learning of Sound Localization Among Blind Individuals - Qian Tao; Chetwyn C. H. Chan; Yue-jia Luo; Jian-jun Li; Kin-hung Ting; Zhong-lin Lu; Susan Whitfield-Gabrieli; Jun Wang; Tatia M. C. Lee (Brain Topography, 2017)

Overexpression of the ascorbate peroxidase gene from eggplant and sponge gourd enhances flood tolerance in transgenic Arabidopsis - Chih-Ming Chiang; Chiu-Chen Chen; Shi-Peng Chen; Kuan-Hung Lin; Li-Ru Chen; Yu-Huei Su; His-Cheng Yen (Journal of Plant Research, 2017)

miRNA Expression Change in Dorsal Root Ganglia After Peripheral Nerve Injury - Hsueh-Ling Chang; Hung-Chen Wang; Yi-Ta Chunag; Chao-Wen Chou; I-Ling Lin; Chung-Sheng Lai; Lin-Li Chang; Kuang-I Cheng (Journal of Molecular Neuroscience, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Development, characterization and cross-species amplification of new microsatellite primers from an endemic species Cinnamomum kanehirae (Lauraceae) in Taiwan - Kuo-Hsiang Hung; Chia-Hung Lin; Huei-Chuan Shih; Yu-Chung Chiang; Li-Ping Ju (Conservation Genetics Resources, 2014)

Influence of gene flow on divergence dating – implications for the speciation history of Takydromus grass lizards - Shu‐Ping Tseng; Shou‐Hsien Li; Chia‐Hung Hsieh; Hurng‐Yi Wang; Si‐Min Lin (Molecular Ecology, 2014)
Dating the time of divergence and understanding speciation processes are central to the study of the evolutionary history of organisms but are notoriously difficult. The difficulty is largely rooted in variations in the ancestral population size or in the genealogy variation across loci. To depict the speciation processes and divergence histories of three monophyletic Takydromus species endemic to Taiwan, we sequenced 20 nuclear loci and combined with one mitochondrial locus published in GenBank. They were analysed by a multispecies coalescent approach within a Bayesian framework. Divergence dating based on the gene tree approach showed high variation among loci, and the divergence was estimated at an earlier date than when derived by the species‐tree approach. To test whether variations in the ancestral population size accounted for the majority of this variation, we conducted computer inferences using isolation‐with‐migration ( IM ) and approximate Bayesian computation ( ABC ) frameworks. The results revealed that gene flow during the early stage of speciation was strongly favoured over the isolation model, and the initiation of the speciation process was far earlier than the dates estimated by gene‐ and species‐based divergence dating. Due to their limited dispersal ability, it is suggested that geographical isolation may have played a major role in the divergence of these Takydromus species. Nevertheless, this study reveals a more complex situation and demonstrates that gene flow during the speciation process cannot be overlooked and may have a great impact on divergence dating. By using multilocus data and incorporating Bayesian coalescence approaches, we provide a more biologically realistic framework for delineating the divergence history of Takydromus .

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

Using ADABOOST and Rough Set Theory for Predicting Debris Flow Disaster - Ping-Feng Pai; Lan-Lin Li; Wei-Zhan Hung; Kuo-Ping Lin (Water Resources Management, 2014)

The Role of Pentacyclic Triterpenoids in the Allelopathic Effects of Alstonia scholaris - Chao-Min Wang; Hsiao-Ting Chen; Tsai-Chi Li; Jen-Hsien Weng; Yun-Lian Jhan; Shi-Xun Lin; Chang-Hung Chou (Journal of Chemical Ecology, 2014)

Arbuscular mycorrhizal fungi induced differential Cd and P phytoavailability via intercropping of upland kangkong (Ipomoea aquatica Forsk.) with Alfred stonecrop (Sedum alfredii Hance): post-harvest study - Junli Hu; Jintian Li; Fuyong Wu; Shengchun Wu; Zhihong Ye; Xiangui Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2013)

Molecular Characterization of an Atypical IncX3 Plasmid pKPC-NY79 Carrying bla KPC-2 in a Klebsiella pneumoniae - Pak-Leung Ho; Yuk-Yam Cheung; Wai-U Lo; Zhen Li; Kin-Hung Chow; Chi-Ho Lin; Jasper Fuk-Woo Chan; Vincent Chi-Chung Cheng (Current Microbiology, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Dynamics of cadmium concentration in contaminated rice paddy soils with submerging time - Jang-Hung Huang; Shan-Li Wang; Jhin-Hao Lin; Yue-Ming Chen; Ming-Kuang Wang (Paddy and Water Environment, 2013)

Biogeochemical cycling of ferric oxyhydroxide affecting As partition in groundwater aquitard - Sheng-Wei Wang; Chen-Wuing Liu; Kuang-Liang Lu; Li-Hung Lin (Environmental Geochemistry and Health, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Effects of the multiple polyadenylation signal AAUAAA on mRNA 3′-end formation and gene expression - Hsin-Hung Lin; Li-Fen Huang; Hsiao-Chien Su; Shih-Tong Jeng (Planta, 2009)

Single-Trial Analysis of Cortical Oscillatory Activities During Voluntary Movements Using Empirical Mode Decomposition (EMD)-Based Spatiotemporal Approach - Po-Lei Lee; Li-Zen Shang; Yu-Te Wu; Chih-Hung Shu; Jen-Chuen Hsieh; Yung-Yang Lin; Chi-Hsun Wu; Yu-Lu Liu; Chia-Yen Yang; Chia-Wei Sun; Kuo-Kai Shyu (Annals of Biomedical Engineering, 2009)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

New Molecular Insights into Cellular Survival and Stress Responses: Neuroprotective Role of Cellular Prion Protein (PrPC) - Raymond Yen-Yu Lo; Woei-Cherng Shyu; Shinn-Zong Lin; Hsiao-Jung Wang; Shun-Sheng Chen; Hung Li (Molecular Neurobiology, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Gene stacking in Phalaenopsis orchid enhances dual tolerance to pathogen attack - Yuan-Li Chan; Kuang-Hung Lin; Sanjaya; Li-Jen Liao; Wen-Huei Chen; Ming-Tsair Chan (Transgenic Research, 2005)

Expression studies of mutations underlying Taiwanese Hunter syndrome (mucopolysaccharidosis type II) - Jui-Hung Chang; Shuan-Pei Lin; Shu-Chuan Lin; Kai-Li Tseng; Chia-Ling Li; Chih-Kuang Chuang; Guey-Jen Lee-Chen (Human Genetics, 2005)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

The Heterogeneity in Risk Factors of Lung Cancer and the Difference of Histologic Distribution between Genders in Taiwan - Chien-Hung Lee; Ying-Chin Ko; Li Shu-Chuan Cheng; Ying-Chao Lin; Hsiang-Ju Lin; Ming-Shyan Huang; Jhi-Juh Huang; Eing-Long Kao; Hwei-Zu Wang (Cancer Causes & Control, 2001)